An encyclopaedic dictionary of modern Indian history (1757-1947) - Kapoor A.N., Gupta V.P. & others (Radha Publication, New Delhi, 2003)
Economics
UGC X PLAN (2004-2005)
ENGLISH
Keywords: An encyclopaedic dictionary of modern Indian history (1757-1947); Economics; Economics